EFL Como Requisito Para Estudios De Posgrado En Mexico: El Caso De Los Egresados Del Ãrea De Ciencias BiolÃ³gico Agropecuarias y Pesqueras de la Universidad AutÃ³noma de Nayarit - GarcÃa, MarÃa Georgina Ochoa; Ramos, Marcela GarcÃa; Cueto, MarÃa del Carmen HernÃ¡ndez; Cheol, M. A. Yun Sang (European Scientific Journal, ESJ, 2018)
The aim of this study is to get a general overview of the relevance of English as a Foreign Language (EFL) requirement for postgraduate studies in Mexico, since such requirement has been established as one of the main elements of National Quality Postgraduate Programs (PNPC) registered in the National Bureau of Science and Technology (CONACYT) catalog. There are 2,155 programs to be found in such catalog, where 130 of them are cataloged as programs of International Competency; are public university graduates ready to cope with the EFL requirement established in PNPC programs? This research project took a closer look into a group of Mexican university graduates´ EFL proficiency levels fulfilled as both: as a fulfillment bachelor’s degree requirement, and as an entry requirement to be accepted in a biological and agropecuary sciences masters’ degree program from the PCPN.